The Relationship Between Maternal Age, Nutritional Knowledge, and Complementary Feeding (Mp-Asi) Parenting Practices with the Incidence of Undernutrition in Toddlers - Purnama, Wulan; Masfufah, Masfufah; Nurdiana, Nurdiana (jitek, 2025)
The assessment of undernutrition status in toddlers was conducted using the weight-for-length or weight-for-height index (WLH or WHH), with a range of -3 to < -2 standard deviations (SD). This study aims to analyze the relationship between maternal age at pregnancy, mothers' nutritional knowledge, and parenting practices in complementary feeding (MP-ASI) with the incidence of undernutrition in toddlers aged 6-23 months. This research employed a cross-sectional design with a population of toddlers aged 6-23 months. A total of 98 toddlers were selected as samples through a cluster random sampling technique. Data collection was conducted through anthropometric measurements, including the weight and length/height of the toddlers, along with questionnaires to assess mothers' knowledge levels and MP-ASI parenting practices. The collected data were analyzed using the chi square test. The results of the analysis showed that maternal age at pregnancy did not have a significant relationship with the incidence of undernutrition in toddlers aged 6-23 months, with a p-value of 0.152 (p > 0.1). However, mothers' nutritional knowledge and MP-ASI parenting practices showed a significant relationship with the incidence of undernutrition in toddlers, with a p-value of 0.000 (p < 0.1). In conclusion, low levels of maternal nutritional knowledge and inadequate MP-ASI parenting practices are associated with undernutrition in toddlers aged 6-23 months. In contrast, maternal age at pregnancy, whether below 20 or above 35, does not show a significant relationship with toddler nutrition status in this study.